La inteligencia emocional que presentan los jóvenes universitarios del municipio de Chinchiná (2022)
The objective of this research work is to analyze the meaning of Emotional Intelligence in young university students in the municipality of Chinchiná, since it has been catalogued, for years, as one of the most violent municipalities at a national level, recognized by micro trafficking, by femicides that are constantly appearing on the front page of local news and newspapers, by a history of drug addiction that has affected the children and youth of the municipality and an endless number of situations that daily resound in the ears of the new generations.